Deleuze's New Image of Thought: Challenging the Dogmatic Image of Thought in Qualitative Inquiry. (November 2017) - Hein, Serge F.
For Deleuze, modern philosophy presupposes a dogmatic image of thought, one that precedes thinking itself. Deleuze engages in a radical critique of this dogmatic image and rejects both common sense and the form of representation. Changes occurred over time in Deleuze's thinking about thought and images, but ultimately, he advocated a new image of genuine, nonrepresentational thought. In his final philosophical work, this new image of thought is equated with the plane of immanence. Thus, the new image of thought provides the basis for the development and use of all other concepts in research. Mainstream qualitative research shares in the same dogmatic image of thought that philosophy presupposes. Two qualitative works that challenge aspects of the dogmatic image of thought in mainstream qualitative inquiry are examined. My use of Deleuze's new image of thought as a method of inquiry in my own qualitative research is also discussed.